The Rise and Fall of Humor: Psychological Distance Modulates Humorous Responses to Tragedy. (July 2014) - McGraw, A. Peter; Williams, Lawrence E.; Warren, Caleb
Humor is a ubiquitous experience that facilitates coping, social coordination, and well-being. We examine how humorous responses to a tragedy change over time by measuring reactions to jokes about Hurricane Sandy. Inconsistent with the belief that the passage of time monotonically increases humor, but consistent with the benign violation theory of humor, a longitudinal study reveals that humorous responses to Sandy's destruction rose, peaked, and eventually fell over the course of 100 days. Time creates a comedic sweet spot that occurs when the psychological distance from a tragedy is large enough to buffer people from threat (creating a benign violation) but not so large that the event becomes a purely benign, nonthreatening situation. The finding can help psychologists understand how people cope and provide clues to what makes things funny and when they will be funny.